2012
DOI: 10.1136/jnnp-2012-303135
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic dysfunction in parkinsonian disorders: assessment and pathophysiology

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder characterised by motor dysfunction ( parkinsonism) and several non-motor features. Dysautonomia is a significant non-motor feature as well as a neuropsychiatric symptom. Autonomic dysfunction can occur even in the early stages of PD, often preceding the onset of the classic motor symptoms of PD. The patterns of autonomic features in PD are different from other parkinsonian disorders. Detection of autonomic dysfunction may therefore be helpful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 89 publications
1
87
0
3
Order By: Relevance
“…PD is frequently associated with symptoms of Autonomic Nervous System (ANS) dysfunction and/or failure [26], including cardiovascular, sexual, bladder, gastrointestinal, and sudo-motor abnormalities [2]. These clinical evidences are in agreement with the results of pathological studies demonstrating how the degenerative process in PD involves subcortical structures, brainstem and medullary autonomic centres as well as post-ganglionic sympathetic fibers [30].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…PD is frequently associated with symptoms of Autonomic Nervous System (ANS) dysfunction and/or failure [26], including cardiovascular, sexual, bladder, gastrointestinal, and sudo-motor abnormalities [2]. These clinical evidences are in agreement with the results of pathological studies demonstrating how the degenerative process in PD involves subcortical structures, brainstem and medullary autonomic centres as well as post-ganglionic sympathetic fibers [30].…”
Section: Introductionsupporting
confidence: 78%
“…While cardiovascular dysautonomia has traditionally been associated with the later stages of PD, it has recently become evident that it can occur at any disease stage, and that its onset can even precede the appearance of motor symptoms [2,18,50]. Previous studies have reported a variable prevalence of cardiovascular autonomic dysfunction in PD, ranging from 23% to 80% as determined by studies which included cohorts of between 20 and 91 patients [3, 29,35].…”
Section: Introductionmentioning
confidence: 99%
“…The similar heart rate responses to orthostasis and exercise in the INC and DEC groups might suggest that the ability to increase/maintain cardiac output was not the likely mechanism contributing to the impaired blood pressure control in the DEC group, consistent with other autonomic failure disorders that display a preserved cardiac output, yet impaired blood pressure, response to exercise [14,15]. That said, stroke volume (and cardiac output) was not assessed in the present study, cardiac sympathetic denervation is common in Parki so 's disease [1], and an impaired cardiac contractility during exercise has also been reported in PD patients with cardiac sympathetic denervation [11] suggesting that an impaired cardiac output response may have occurred in the DEC group. In contrast, it is possible that the control of total peripheral resistance is impaired in the DEC group.…”
Section: Discussionmentioning
confidence: 57%
“…The proposed mechanisms of cardiovascular autonomic dysfunction in Parki so 's disease generally involve lewy body accumulation and cell loss in various key areas of the autonomic nervous system, such as, autonomic regulatory areas including the hypothalamus, medulla, locus coeruleus and raphe, pre-ganglionic parasympathetic and sympathetic regions including the dorsal vagal motor nuclei of the glossopharyngeal and vagal nerves, autonomic and sympathetic ganglia, as well as post-ganglionic sympathetic denervation [1] that ultimately affect control of blood pressure through baroreflex impairment and loss of sympathetic innervation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation